2022
DOI: 10.1111/ecog.06465
|View full text |Cite
|
Sign up to set email alerts
|

Insights into natal origins of migratory Nearctic hover flies (Diptera: Syrphidae): new evidence from stable isotope (δ2H) assignment analyses

Abstract: Hover flies (Diptera: Syrphidae) are an important group of insects that provide a multitude of key ecosystem services including pollination and biological control, yet many of their major life history traits are not understood. Some Palearctic hover fly species are known to migrate in response to changing seasonal conditions, yet this behavior is almost entirely unrecognized in Nearctic species. At least one species, Eupeodes americanus, is partially migratory during autumn while Allograpta obliqua may be non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 77 publications
1
6
0
Order By: Relevance
“…The δ 2 H values of M. separata and S. frugiperda forewings were also linearly correlated with the δ 2 H values of maize leaves (Table 5, Figures 1, 2). These results are consistent with previous studies (Hobson et al, 1999b, 2018; Holder, 2012; Clem et al, 2022).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The δ 2 H values of M. separata and S. frugiperda forewings were also linearly correlated with the δ 2 H values of maize leaves (Table 5, Figures 1, 2). These results are consistent with previous studies (Hobson et al, 1999b, 2018; Holder, 2012; Clem et al, 2022).…”
Section: Discussionsupporting
confidence: 94%
“…Experimental studies showed that 30% to 50% of hydrogen was incorporated from water sources through the consumption of water or food in birds (Hobson et al, 1999a;Wolf et al, 2011), humans (Ehleringer et al, 2008), aquatic invertebrates (Nielson & Bowen, 2010;Solomon et al 2009;Wang et al, 2009), and terrestrial insects (Hobson et al,1999bHolder, 2012;Clem et al, 2022). To understand the natal origin of animal growth, the isotopic composition of hydrogen derived from water in diets and animal tissues must be revealed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No further observations being made in the 90+ years since, and the status of these movements is currently unknown (Menz, Brown, et al, 2019). However, recent isotopic studies on the Syrphid Eupeodes americana suggest that these flies are capable of moving up to 3000 km from Canada to Alabama, indicating that the flyway down the eastern part of North America is long distance and may still be well-utilised by migratory Diptera (Clem et al, 2023) along with other migratory insects (Howard & Davis, 2009; Wikelski et al, 2006). In contrast, only one movement has been identified on the western seaboard, a northward movement of presumed Eupeodes sp.…”
Section: Global Distribution and Flywaysmentioning
confidence: 99%
“…Although these studies shed light on the migratory behavior of lepidopteran pests ( Westbrook 2008 , Tessnow et al 2023 ), the geographic limitations of these studies pose challenges to comprehensive measurements and the predictability of large-scale movements. An attractive and innovative approach to overcome these challenges is the use of stable isotope techniques associated with standardized predictive geospatial modeling approaches, which can provide rapid, cost-effective, and precise solutions compared to other methods used to track insect migration patterns on a continental scale ( Courtiol et al 2019 , Clem et al 2023 , Dittemore et al 2023 ). Stable isotopes have long been used to identify geographically distinct animal populations, with variations in stable isotope ratios within food webs serving as natural markers that can be linked to origin ( Vogel et al 1990 , Hobson 1999 ).…”
Section: Introductionmentioning
confidence: 99%